Cosmic Imagery in Russian Poetry at Turn of 18th and 19th Centuries: Strategies of Study - K. A. Potashova (Научный диалог, 2023)
The article explores the mechanisms of poetic representation of celestial bodies, the celestial sphere, and extraordinary cosmic phenomena in Russian poetry at the turn of the 18th and 19th centuries in the context of changing artistic paradigms (classicism and romanticism), poets’ worldview, and their artistic methods. It analyzes literary-critical articles from the 1820s-1840s and works by literary scholars from the second half of the 19th to the 21st centuries. The main research strategies for analyzing the cosmic imagery in Russian poetry of this period are identified. The existing methodology for interpreting the poetic works of G. R. Derzhavin and V. A. Zhukovsky, who were at the forefront of the leading artistic systems of the time, is evaluated in terms of understanding the image of the cosmic universe. It is determined that in literary criticism and scholarship, three main approaches have emerged in interpreting the image of the cosmic universe: interpretations of the astronomical universe as classical emblems, as typical elements of landscape in romantic aesthetics, and as ontologically charged images. It is proven that the study of cosmic motifs did not have a systematic character in relation to the literary process at the turn of the 18th and 19th centuries.